The Transformational Leadership of the Female Leader in Pesantren - Rahayu, Eka Adni; Faraz, Nahiyah Jaidi (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2019)
This study aims to reveal three leadership elements of the female leader at Nurul Ummah Putri Islamic Boarding School (PPNU-Pi) by exploring the nature of leadership, the decision-making process, and the leadership style. This study is grounded on qualitative research using a case study approach through interviews, observation, and documentation. This study highlights that nyai as the female leader at PPNU-Pi possesses a firm, caring, intelligent, straightforward, communicative, and optimistic nature of leadership. The decision-making process at PPNU-Pi is conducted in a relatively modern way. It starts with identifying the problem. Then, it will be followed by looking for alternative solutions. After selecting alternatives which are conducted together with the female leader, they will implement the solution. After applying the solution, there is a trial period to see how effective the solution has been implemented. Finally, this study discusses the implementation of female leader leadership in PPNU-Pi, which represents essential characteristics of transformational leadership such as female leader as an ideal influence, inspirational and motivational leader, and intellectual stimulators.Â